2002
DOI: 10.1002/ajh.10108
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of Bcl‐2 family proteins in myelodysplastic syndromes

Abstract: Excessive apoptosis is implicated in the pathogenesis of myelodysplastic syndromes (MDS). We assessed by flow cytometry the expression of several members of the Bcl-2 family in bone marrow mononuclear cells (BMMNC) of 168 MDS samples at diagnosis. The proteins studied were Bcl-2, Bcl-xL (anti-apoptotic), Bax, Bad, Bak, and Bcl-xS (pro-apoptotic). The percentage of BMMNC expressing Bcl-2 and Bcl-xL was higher in refractory anemia with excess of blasts (RAEB), RAEB in transformation (RAEB-T), and chronic myelomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 47 publications
2
52
0
5
Order By: Relevance
“…19 Similarly, Bcl2 expression was higher in AML cells arising in NHD13 mice ( Figure 3A). Therefore, the NHD13 mouse model of MDS parallels the temporal changes in BCL2-related proteins seen in human MDS.…”
Section: Bcl2 Prevents Apoptosis and Restores Blood Countsmentioning
confidence: 83%
“…19 Similarly, Bcl2 expression was higher in AML cells arising in NHD13 mice ( Figure 3A). Therefore, the NHD13 mouse model of MDS parallels the temporal changes in BCL2-related proteins seen in human MDS.…”
Section: Bcl2 Prevents Apoptosis and Restores Blood Countsmentioning
confidence: 83%
“…These technical aspects coupled to lower patient numbers may have accounted for the failure to detect a correlation between disease progression and NF-kB activation. [67][68][69] Indeed, the expression of proapoptotic proteins of the Bcl-2 family like Bak, Bad, and Bcl-X S has a favorable prognostic value in MDS, while the expression of antiapoptotic proteins like Bcl-2 and Bcl-X L is associated with unfavorable prognostic value, suggesting that apoptosis suppression could be implicated in the transformation of MDS to AML. 68 XIAP overexpression has also been implicated in apoptosis suppression and transformation of MDS to AML.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%
“…[67][68][69] Indeed, the expression of proapoptotic proteins of the Bcl-2 family like Bak, Bad, and Bcl-X S has a favorable prognostic value in MDS, while the expression of antiapoptotic proteins like Bcl-2 and Bcl-X L is associated with unfavorable prognostic value, suggesting that apoptosis suppression could be implicated in the transformation of MDS to AML. 68 XIAP overexpression has also been implicated in apoptosis suppression and transformation of MDS to AML. 69 A deregulation of FLIP and its splice variants in MDS bone marrow has also been shown recently.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%
“…High Bcl-x L levels correlate with a poorer prognosis in patients with intermediate-grade lymphomas (Bairey et al, 1999), squamous cell carcinoma of the oropharyx (Aebersold et al, 2001), soft-tissue sarcomas (Kohler et al, 2002), and myelodysplastic syndrome (Boudard et al, 2002). Assays examining the ability of cells to regrow after drug treatment in vitro and in vivo have not only established the ability of Bcl-x L to enhance tumor cell repopulation after cytotoxic insults (Simonian et al, 1997;Liu et al, 1999), but also suggested that Bcl-x L is a more potent inducer of cell survival under these conditions (Simonian et al, 1997).…”
Section: How To Study the Role Of Apoptosis In Drug Resistancementioning
confidence: 99%